2011
DOI: 10.4028/www.scientific.net/amr.396-398.1918
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation Degradation Behavior on Fracturing Wastewater in Oilfield

Abstract: Due to great variety additives and disposal difficulty, chemical method, biochemical method and solidification are adopted to treat fracturing wastewater in oil field. These processes easily bring about shortcomings, including high cost and secondary pollution. Studied on the treatment of fracturing wastewater of 4# well in Sichuan Oilfield by modified bentonite loading TiO2-Ag2O composite catalyst, COD removal rate is determined for different condition of pH value of solution, adding content of TiO2, inflatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…When TiO 2 was used to treat hydrocarbons in oily wastewater, it was found that the reaction was more favorable under strong acidic conditions. Wang [ 37 ] pointed out that pH had an important effect on the photoreaction process, not only on the surface charge distribution of TiO 2 particles, but also on the hydroxyl radical (·OH). The increase in H + concentration will be more conducive to the formation of the hydroxyl radical (·OH).…”
Section: Photocatalysis Technologymentioning
confidence: 99%
“…When TiO 2 was used to treat hydrocarbons in oily wastewater, it was found that the reaction was more favorable under strong acidic conditions. Wang [ 37 ] pointed out that pH had an important effect on the photoreaction process, not only on the surface charge distribution of TiO 2 particles, but also on the hydroxyl radical (·OH). The increase in H + concentration will be more conducive to the formation of the hydroxyl radical (·OH).…”
Section: Photocatalysis Technologymentioning
confidence: 99%
“…However, their approach did not encompass the reuse of the fracturing fluid post-reflow [5,6] . Conversely, Wan et al employed catalysts to treat fracturing wastewater, an approach that inadvertently escalates treatment expenditures [7,8] of 9% to 35% for recycled fracturing fluids. Yoxtheimer reported an average well recovery rate of 10% for return fluids in the Marcellus.…”
Section: Introductionmentioning
confidence: 99%